OP0103 Comparative Effectiveness of Tai Chi Versus Physical Therapy in Treating Knee Osteoarthritis: A Randomized, Single-Blind Trial. (9th June 2015) - Wang, C.; Iversen, M.; McAlindon, T.; Harvey, W.F.; Wong, J.; Fielding, R.; Driban, J.; Price, L.L.; Schmid, C.
Abstract : Background: Knee osteoarthritis (OA) causes long-term pain and few medical remedies effectively influence the course of the disease. Our previous work demonstrated that Tai Chi can improve both physical and psychological health among patients with chronic pain conditions (1). Objectives: This study is the first randomized, single-blind trial of Tai Chi versus a standard Physical Therapy regimen for patients with symptomatic and radiographic Knee OA. Methods: In this study, adults ≥40 years of age satisfying American College of Rheumatology criteria for Knee OA were randomized to 12 weeks of Tai Chi (2x/week) using classical Yang style or to a standard Physical Therapy regimen (2x/week for 6 weeks, followed by 6 weeks of rigorously monitored home exercise). The study physician and outcomes assessments were blinded to treatment allocation. The primary outcome was change in pain measured by the Western Ontario and McMaster Universities (WOMAC) subscale at 12 weeks. Secondary outcomes included change in WOMAC function domain scores, patient global assessment (VAS, 0-10 cm), depression (Beck II), chronic pain self-efficacy (0-10), 20 meter walk test (sec) and 6 min walk test (meters), and quality of life (SF-36, 0-100), at 12, 24 and 52 weeks. Both groups were compared using an intent-to-treat analysis. Results: 204 adults were randomized: 106 to Tai Chi and 98 to Physical Therapy. The mean age of participants was 60 y (SD 10.5), mean disease duration 8 y (SD 10.1), mean BMI, 33 kg/m 2 (SD 7.2), 70% were female, and 53% were white. There were no significant differences in baseline characteristics between treatment groups. Participants' baseline expectations of benefit from an exercise intervention were similar between the groups [Tai Chi =4.0 (SD 0.8), Physical Therapy =4.1 (SD 0.7)]. At 12 weeks, WOMAC pain scores declined by 167 points (95% CI: 144, 190) in the Tai Chi group and by 143 points (95% CI: 119, 167) in the Physical Therapy group. Though both groups improved significantly, there was no significant difference between groups in WOMAC pain improvement (p=0.16). Most outcomes (WOMAC pain and function, patient global assessment, self-efficacy, 20 meter and 6 minute walk tests and SF-36 Physical Component Summary) demonstrated sustained improvement in both treatment groups at 12 weeks. A significantly greater improvement in the Tai Chi group was found in the SF-36 Physical Component Summary (3.2; 95% CI: 0.8, 5.5) and the Beck depression score (2.7; 95% CI, 0.7, 4.8). No significant differences between groups were found for other outcomes at 12 weeks. No serious adverse events were observed. Conclusions: Tai Chi was as effective as standard Physical Therapy in reducing pain and improving physiological and psychological functioning of participants with knee OA with a similar safety profile. References: Wang C, Iversen MD, McAlindon T, et al. Assessing the comparative effectiveness of Tai Chi versus physical therapy for knee osteoarthritis: design and rationale for a randomized trial. BMC Complement Altern Med. 2014 Sep 8;14:333. doi: 10.1186/1472-6882-14-333. PubMed PMID: 25199526. Acknowledgements: Supported by R01 AT005521 from the National Center for Complementary and Integrative Health of the National Institutes of Health. Disclosure of Interest: None declared